1991
DOI: 10.1523/jneurosci.11-03-00641.1991
|View full text |Cite
|
Sign up to set email alerts
|

A direct demonstration of functional specialization in human visual cortex

Abstract: We have used positron emission tomography (PET), which measures regional cerebral blood flow (rCBF), to demonstrate directly the specialization of function in the normal human visual cortex. A novel technique, statistical parametric mapping, was used to detect foci of significant change in cerebral blood flow within the prestriate cortex, in order to localize those parts involved in the perception of color and visual motion. For color, we stimulated the subjects with a multicolored abstract display containing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

93
926
12
18

Year Published

1997
1997
2015
2015

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 1,599 publications
(1,049 citation statements)
references
References 39 publications
93
926
12
18
Order By: Relevance
“…An early visual region (V1) was identified using a contrast testing for the effect of visual stimulation. An extrastriate cortex (motion-sensitive area V5; Zeki et al, 1991) was identified using a test for motion-specific responses, and an attentional area was identified in the frontal eye fields (FEF), using a test for the effects of attention (see Fig. 1 for details).…”
Section: Empirical Datamentioning
confidence: 99%
“…An early visual region (V1) was identified using a contrast testing for the effect of visual stimulation. An extrastriate cortex (motion-sensitive area V5; Zeki et al, 1991) was identified using a test for motion-specific responses, and an attentional area was identified in the frontal eye fields (FEF), using a test for the effects of attention (see Fig. 1 for details).…”
Section: Empirical Datamentioning
confidence: 99%
“…It is independent of stimulus color but highly sensitive to luminance contrast. Most prominently, neurons in V5/ MTĂŸ are highly direction selective and respond to the presentation of moving stimuli and edge-contrast as seen in pattern-reversal stimuli (5)(6)(7)(8). V5/MTĂŸ was found to play a role concerning the well-known motion aftereffect (MAE), that is, the ongoing illusionary perception of motion in the opposite direction after a period of viewing unidirectional motion (9)(10)(11)(12).…”
Section: Introductionmentioning
confidence: 99%
“…1989; Zeki et al. 1991; McKeefry and Zeki 1997). The stimuli were created using the Psychophysics Toolbox (Brainard 1997; RRID:rid_000041) running on MATLAB (The Mathworks, Sherborne, MA, USA) and back‐projected onto an LCD screen located inside the bore of the scanner.…”
Section: Methodsmentioning
confidence: 99%